Larsen’s cairn: the birth of a new historical site in Antarctica - Fontana, Pablo Gabriel; Guerriere, María Angélica (Polar research, 2025)
This article describes the history of Larsen’s cairn, one of the oldest historical sites in Antarctica, and explains how it became one of the most recently declared Historical Site and Monuments (HSMs) on the continent. Norwegian explorer and whaler Carl Anton Larsen constructed the cairn on Marambio/Seymour Island during the Norwegian Whaling Expedition in 1892. Officially designated as C.A. Larsen Multiexpedition Cairn (HSM 94), this site featured in several episodes of Antarctic history, spanning three periods of Antarctic history: Antarctic whaling, the Heroic Age of Antarctic exploration, and a period characterized by the installation of permanent stations at the end of World War II. Argentina, Norway, Sweden and the UK have all had some involvement in the cairn and all four nations now share an administrative role vis-à-vis the HSM, making it the HSM with the largest number of administrators to date. Adding to its significance, the cairn is linked to the earliest phase of invertebrate palaeontology in Antarctica and can also be considered the first material remains of the Norwegian presence in Antarctica.